2021
DOI: 10.1002/ece3.8088
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of pseudoscorpion diversity: The German Barcode of Life campaign reveals high levels of undocumented diversity in European false scorpions

Abstract: DNA barcoding is particularly useful for identification and species delimitation in taxa with conserved morphology. Pseudoscorpions are arachnids with high prevalence of morphological crypsis. Here, we present the first comprehensive DNA barcode library for Central European Pseudoscorpiones, covering 70% of the German pseudoscorpion fauna (35 out of 50 species). For 21 species, we provide the first publicly available COI barcodes, including the rare Anthrenochernes stellae Lohmander, a species protected by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 68 publications
(98 reference statements)
4
28
0
Order By: Relevance
“…In contrast, large intraspecific distance ranging from 0% to as much as 17.3% was noticed for COI genes in pseudoscorpions, which distorts the pattern of intra- and interspecific variation and spoils the existence of a barcode gap. This observation may result from undocumented species diversity, but also from anomalies in the COI evolution of these arachnids, indicating variable molecular change between species within different taxa (Muster et al 2021 ).…”
Section: How To Get a Barcodementioning
confidence: 99%
“…In contrast, large intraspecific distance ranging from 0% to as much as 17.3% was noticed for COI genes in pseudoscorpions, which distorts the pattern of intra- and interspecific variation and spoils the existence of a barcode gap. This observation may result from undocumented species diversity, but also from anomalies in the COI evolution of these arachnids, indicating variable molecular change between species within different taxa (Muster et al 2021 ).…”
Section: How To Get a Barcodementioning
confidence: 99%
“…Further studies are required to determine whether E. boldorii is more widespread in Central Europe than assumed by Muster et al (2004), or whether another cryptic species could be involved (cf. Muster et al 2021). Also, other aspects of the distribution need to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…and was found in eastern Slovakia in the Slovak Karst( Jászayová & Christophoryová 2019, Jászayová & Jászay 2021. Based on a recent molecular analysis(Muster et al 2021), this species was shown to exhibit high levels of cryptic diversity, which suggests that may consist of several, as yet undescribed, species. Future research with molecular methods appears to be necessary.…”
mentioning
confidence: 98%
“…Phylogenetic analyses were performed using a maximum likelihood (ML) 40 approach in IQ-TREE ver. 2.0.3 41 with 5000 ultrafast bootstraps 42 for: (i) the Dinaric dataset and additional sequences from central Europe 43 to check species-level determination (Supplementary File 1 online), and ii) Dinaric COI haplotypes only to select taxonomically relevant sequences for detailed analyses (Fig. 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we examined relationships among populations of Neobisium sylvaticum (C.L. Koch, 1835) from Croatia and Germany, using published sequences 43 (Supplementary Fig. 2 online).…”
Section: Methodsmentioning
confidence: 99%